2017
DOI: 10.1080/08897077.2016.1220443
|View full text |Cite
|
Sign up to set email alerts
|

Recent Incarceration and Buprenorphine Maintenance Treatment Outcomes among Human Immunodeficiency Virus–Positive Patients

Abstract: Background Opioid use disorder is a common cause of morbidity and mortality among people living with HIV/AIDS. Buprenorphine maintenance treatment (BMT) is an effective means of therapy, but patients with recent criminal justice involvement may need more support during BMT than other patients. We hypothesized that recently incarcerated BMT patients who initiated treatment in primary care would have poorer treatment outcomes than those who were not recently incarcerated. Methods We analyzed data from a multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Two studies evaluated the impact of post-release MMT continuation on all-cause and overdose mortality [69] and on criminal recidivism [71]. Five studies evaluated the impact of BPN-based opioid pharmacotherapy post-release on access to and/or retention in addiction treatment, levels of illicit opioid use, and criminal recidivism [70,72,73,76,77]. One RCT compared the efficacy of MMT and naltrexone implants post-release in reducing illicit drug use and criminal recidivism [78], and 3 studies evaluated the impact of NLX kit provision in preventing overdose-related deaths post-release [74,75,79].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies evaluated the impact of post-release MMT continuation on all-cause and overdose mortality [69] and on criminal recidivism [71]. Five studies evaluated the impact of BPN-based opioid pharmacotherapy post-release on access to and/or retention in addiction treatment, levels of illicit opioid use, and criminal recidivism [70,72,73,76,77]. One RCT compared the efficacy of MMT and naltrexone implants post-release in reducing illicit drug use and criminal recidivism [78], and 3 studies evaluated the impact of NLX kit provision in preventing overdose-related deaths post-release [74,75,79].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies evaluated the impact of post-release BPN-based treatments on treatment retention, illicit opioid use, and criminal recidivism [70,72,73,76,77]. Springer et al [76,77] examined data from a group of HIV-positive incarcerated persons with OUD who received BPN/NLX treatment post-release.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV infection and incarceration may interact to augment the underlying pathways leading to opioid-related overdose through cumulative disadvantage. Individuals living with HIV and with a recent history of justice involvement were more likely to be homeless, unemployed and previously diagnosed with a mental illness relative to those with a recent history of justice involvement without HIV [38]. Among people who inject drugs living with HIV, those with recent criminal justice exposure had 25% greater adjusted odds of lapses in medical care relative to those without criminal justice exposure [39].…”
Section: Underlying Factors and Settingmentioning
confidence: 99%
“…In another multisite cohort study, they found that recent incarceration was not associated with any differences in 6-or 12month treatment retention or self-reported opioid use [38]. A large multi-site retrospective cohort study (n = 48, 689) examined national Veterans Health Administration (VHA) clinical and pharmacy records of veterans diagnosed with opioid use disorder and found that veterans with criminal justice involvement had reduced odds of receiving MOUD compared to others [39].…”
Section: Incarceration Status and Buprenorphine Effectivenessmentioning
confidence: 99%